The Evolution of Smartwatches in Continuous Health Monitoring: From Fitness Tracker to Clinical Tool - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Meta Description: Explore the academic and technological evolution of smartwatches in continuous health monitoring. Learn about the shift from basic fitness ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning